Analisis Rasio Keuangan dalam Mengukur Kinerja Keuangan Pada PT. Perusahaan Gas Negara (Persero), Tbk - Nirawati, Lia; Samsudin, Acep; Ramadhan Santoso, Dayyan; Zahrain Adjie, Mohamad; Agni Naenara, Sabhina; Anindhita Netanya, Stevani; Trisnawati, Erica (CV. Lafadz Jaya, 2022)
The purpose of this study was to measure financial performance by applying financial ratio analysis at PT. State Gas Company (Persero), Tbk. In this study using liquidity financial ratios, activity ratios, and solvency ratios. The data source used in this study is secondary data from PT. The State Gas Company (Persero), Tbk in 2016 to 2018. Data collection techniques used documentation techniques. The analytical method is done by comparing company financial performance in several periods. The result of the activity ratio calculation is that the company cannot be said to be efficient when using company assets. The results of the calculation of the company's solvency ratio are not good because the company's debt is bigger than the company's capital. The results of the calculation of the company's liquidity can meet financial obligations in the short term.